2022
DOI: 10.21037/jtd-22-29
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic expression of G protein-coupled estrogen receptor 1 correlates with poor postoperative prognosis in non-small cell lung cancer

Abstract: Background: A hormonal role in the development of non-small cell lung cancer (NSCLC) has been well documented, and the classic estrogen receptors (ERs)-ERα and ERβ have been extensively investigated over the past decade. The expression of ERβ was found to be high and display biological activity in NSCLC, but anti-estrogen therapy targeting this receptor has shown limited efficacy for the disease. The third estrogen receptor, G protein-coupled estrogen receptor 1 (GPER1/GPR30), was recently found to be highly e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Wang et al screened for G protein-coupled receptor-related genes through immune infiltrationrelated genes [60]; Liu et al studied the effects of G protein-coupled receptor antagonists on lung adenocarcinoma [61]; Jala VR, Li ZH, Wu G and Yao S et al studied single gene of G protein coupled receptor [62][63][64][65]; Touge H et al study was the effect of G protein coupled receptor on the morphology of lung adenocarcinoma cells [66]; Khan M's review type of study mainly talked about the relevance of GPCR in the treatment of lung adenocarcinoma [67]; Gao Y and Fujimoto J was mainly experimental and did not use bioinformatics on a large scale [68,69].Our study is G protein-coupled receptor fully characterised and some of the genes have not been studied yet.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al screened for G protein-coupled receptor-related genes through immune infiltrationrelated genes [60]; Liu et al studied the effects of G protein-coupled receptor antagonists on lung adenocarcinoma [61]; Jala VR, Li ZH, Wu G and Yao S et al studied single gene of G protein coupled receptor [62][63][64][65]; Touge H et al study was the effect of G protein coupled receptor on the morphology of lung adenocarcinoma cells [66]; Khan M's review type of study mainly talked about the relevance of GPCR in the treatment of lung adenocarcinoma [67]; Gao Y and Fujimoto J was mainly experimental and did not use bioinformatics on a large scale [68,69].Our study is G protein-coupled receptor fully characterised and some of the genes have not been studied yet.…”
Section: Discussionmentioning
confidence: 99%
“…(or G-15 treatment) increased cisplatin sensitivity [32] AGS and MGC-803 cell lines N.D. Co-expression of cytoplasmic and nuclear GPER expression was associated with a poor prognosis. Nuclear GPER is correlated with ER-β [132] Tissue samples from LC tumors and adjacent normal tissues A549, H23, H1299, H1792, H1395, H1435, H1793, H1944, H2073 (LC), and HPL1D, HBEC2-E, HBEC2-KT, and HBEC3-KT (epithelial lung) cell lines N.D.…”
Section: Gper Induces Cisplatin Resistance By Promoting Emt Gper Acti...mentioning
confidence: 99%
“…Regarding the subcellular localization of GPER, in non-small cell lung cancer (NSCLC) samples (including lung adenocarcinoma and squamous cell carcinoma), it was expressed in both the cytoplasm and nucleus [131,132]. A correlation was found in the expression of GPER and ER-β [131,132]. Moreover, higher cytoplasmic expression of GPER was associated with higher tumor stages with less cell differentiation [131].…”
Section: Lung Cancermentioning
confidence: 99%
“…The GPER1 protein is known to be biologically active and highly expressed in a range of solid tumors, particularly those with sex-based differences in their incidence rates, such as breast, endometrial, thyroid, and colon cancer (Hernandez-Silva et al 2020;Hsu et al 2019;Jacenik et al 2019;Xu et al 2019). Recently, research revealed that GPER1 expression was elevated in NSCLC compared to normal lung tissue (Jala et al 2012), and higher expression correlated with poor postoperative prognosis in NSCLC patients (Li et al 2022). Studies have indicated that the activation of EGFR via GPER1 leads to the phosphorylation of ERK1/2, which promotes the expression of matrix metalloproteinase-2 (MMP-2) and matrix metalloproteinase-9 (MMP-9).…”
Section: Introductionmentioning
confidence: 99%